2015
DOI: 10.3892/ol.2015.3938
|View full text |Cite
|
Sign up to set email alerts
|

Intraluminal superior vena cava metastasis from adenosquamous carcinoma of the duodenum: A case report

Abstract: In 2013, a 76-year-old male with a cardiac pacemaker was diagnosed with adenosquamous carcinoma of the duodenum. Subsequently, a pancreatoduodenectomy and lymph node dissection were performed, and 12 cycles of adjuvant chemotherapy (modified FOLFOX6 regimen), which consisted of fluorouracil, leucovorin and oxaliplatin, were administered via a central venous catheter. At 5 months after the completion of adjuvant chemotherapy, the patient experienced the sudden onset of severe pain at the back right of the ear, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…CTCs (likely in the case of CTC clusters) may become trapped in the post-capillary venules in the lung, spleen, or liver, 169 and upon intraluminal proliferation can give rise to secondary tumors. [170][171][172] CTCs may also hijack mechanisms governing leukocyte recruitment to extravasate from the circulation into the surrounding tissue. In this process, ICAM-1 expressed by ECs will be a key regulatory player.…”
Section: Icam-1 Roles In the Initiation And Progression Of Tumor Metamentioning
confidence: 99%
“…CTCs (likely in the case of CTC clusters) may become trapped in the post-capillary venules in the lung, spleen, or liver, 169 and upon intraluminal proliferation can give rise to secondary tumors. [170][171][172] CTCs may also hijack mechanisms governing leukocyte recruitment to extravasate from the circulation into the surrounding tissue. In this process, ICAM-1 expressed by ECs will be a key regulatory player.…”
Section: Icam-1 Roles In the Initiation And Progression Of Tumor Metamentioning
confidence: 99%
“…Santra et al reported paraneoplastic thrombus formation in SVC due to lung cancer. 5 Moreover, paraneoplastic causes of SVC syndrome due to thrombosis have been reported in association with renal cell carcinoma, 6 ovarian cancer 7 and Richter syndrome. 8 Obstruction of the SVC can also be due to intraluminal metastasis without thrombus formation.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Other nonspecific methods include head elevation, mild diuresis and corticosteroids to decrease swelling and dyspnea. When thrombosis is the cause of SVC syndrome, thrombolysis 1 and/or anticoagulation 1 , 2 , 3 , 4 , 5 may be indicated. Our patient received anticoagulation and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its rarity, the clinicopathological characteristics and survival outcomes of intestinal ASCC have not been clearly determined. The previous reports are summarized in Table I ( [13][14][15][16][17][18][19][20]. Almost all patients had abdominal pain as a chief complaint, and their median age was 76 years (range, 55-80 years).…”
Section: Discussionmentioning
confidence: 99%